Deuterium and 37Chlorine Rich Fluids on the Surface of Mars: Evidence From the Enriched Basaltic Shergottite Northwest Africa 8657. Issue 9 (15th September 2020) - Hu, S.; Lin, Y.; Anand, M.; Franchi, I. A.; Zhao, X.; Zhang, J.; Hao, J.; Zhang, T.; Yang, W.; Changela, H.
Abstract: Apatite, a major hydrous mineral in Martian meteorites, has the potential to reveal history of volatiles on Mars. Here we report the H and Cl isotopic systematics of apatite from the enriched basaltic shergottite Northwest Africa (NWA) 8657 to better understand the processes influencing volatiles at or near the Martian (sub)surface. The apatite in NWA 8657 has the highest reported δD value (up to 6, 509‰) of any phosphates in Martian meteorites. The positive correlation between the H2 O contents (72–2, 251 ppm) and δD values (3, 965–6, 509‰) as well as between the Cl contents (1.28–6.17wt%) and δ 37 Cl values (−1.7–4.0‰) in NWA 8657 apatite are consistent with mixing between volatiles derived from the Martian mantle and meteoric water/fluid. The D‐ and 37 Cl‐enrichment of apatite in NWA 8657 implies isotopic exchange with subsurficial fluids during postcrystallization hydrothermal event(s). Plain Language Summary: Mars was probably a wet and warm world during its earliest geological history, supported by many lines of evidence. Present‐day Mars is cold and arid although recent remote sensing data support the existence of subsurface glaciers and seasonal fluid activities at some locations. In this study, our aim was to use ground truth about the potential water‐rock interaction on or near‐surface environments on recent Mars via measuring the H and Cl isotopic compositions of apatite from a geologically young meteorite from Mars: the enriched basaltic shergottite Northwest Africa (NWA) 8657. The petrography and mineral chemistry of apatite and other associated phases, for example, merrillite, maskelynite, mesostasis, and pyroxene, were documented prior to in situ H and Cl isotopes analysis. The water contents of apatite, merrillite, maskelynite, mesostasis, and pyroxene are positively correlated with the δD values. All of the data sets can be reconciled in terms of mixing between two end‐members, a D‐poor ( 0‰) mantle reservoir and a D‐rich (5, 920 ± 500‰) near‐surface/underground water reservoir. Moreover, apatite in NWA 8657 displays 37 Cl‐enriched ( 1 ± 1‰ in average) characteristics. These signatures are consistent with D‐ and 37 Cl‐rich fluid‐assisted isotopic exchange in recent near‐surface environment on Mars. Key Points: First report of H and Cl isotopic systematics of apatite from the Martian meteorite NWA 8657 NWA 8657 apatite has the highest reported δD value (up to 6, 509‰) of any phosphates in Martian meteorites The H and Cl isotopic compositions of apatite in NWA 8657 imply D‐ and 37 Cl‐rich fluids on surface of Mars